2019
DOI: 10.1007/s11837-019-03471-2
|View full text |Cite
|
Sign up to set email alerts
|

Al8Mn5 Particle Settling and Interactions with Oxide Films in Liquid AZ91 Magnesium Alloys

Abstract: Al 8 Mn 5 particles form as primary solidification phases in Mg-Al-based alloys and are important for ensuring adequate corrosion resistance. However, excessive Al 8 Mn 5 formation above the a-Mg liquidus temperature can lead to sludge formation, and the clustering of Al 8 Mn 5 particles on oxide films can generate deleterious casting defects. Here, we use analytical SEM and realtime synchrotron x-ray radiography to study Al 8 Mn 5 particle settling, the formation of a sludge layer, and the mechanism of Al 8 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Most films were highly contorted (Fig. 4a, b), which was very similar to the ''snaky'' entrained oxides film found by previous researchers [30][31][32][33]. Upon investigation, it was found that the entrained films often wrapped at least one, although often several, collapsed bubbles as an integral part of the defects structure.…”
Section: Resultssupporting
confidence: 80%
“…Most films were highly contorted (Fig. 4a, b), which was very similar to the ''snaky'' entrained oxides film found by previous researchers [30][31][32][33]. Upon investigation, it was found that the entrained films often wrapped at least one, although often several, collapsed bubbles as an integral part of the defects structure.…”
Section: Resultssupporting
confidence: 80%
“…Furthermore, Fe-containing phases can be found, which are Al2Fe in AX22 and Al5Fe2 in AX32. The lower Fe-content in AX32 compared to AX22 can be due to settling of Mn-Fe particles in the melt before casting the material [33]. According to the calculation, the Fe-content in Al8Mn5 is negligible, while according to the literature, this phase plays an important role in binding Fe [34].…”
Section: Microstructurementioning
confidence: 88%
“…Synchrotron radiation X-rays with high brilliance and coherency have allowed us to observe solidification and related phenomena for various alloy systems over the last two decades. So far, observable alloy systems have been extended from low-melting-temperature alloys (Sn, Zn, Al, Mg alloys) [1][2][3][4][5][6][7][8] to high-melting-temperature alloys (copper, Ni-based superalloy, cast iron, carbon steel, stainless steel) [9][10][11][12]. Even a reactive Ti alloy has been achieved [13].…”
Section: Introductionmentioning
confidence: 99%